FAKTOR BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS LUBUK TAROK - Febriniwati Rifdi; Nita Tri Putri; Metri Eliza (Maternal Child Health Care, 2021)
Maternal and child nutritional and health status is a determinant of the quality of human resources. They also critical period before pregnancy, during pregnancy and while breastfeeding. Based on initial survey in Lubuk Tarok Community Health Center, The purpose of this study was to determine Factors Related to Stunting in Toddlers in Lubuk Tarok Community  Health Center, Sijunjung Regency in 2019. The type of this study was analytic descriptive with case control study approach. It was conducted in Lubuk Tarok Community Health Center. There were  47 subject for each group which were selected by purposive sampling technique. The data were analyzed by Chi-Square test with 95% confidence level. The results of this study showed 47 (50%) suffered from stunting, 57 (60.6%) did not provide exclusive breastfeeding, 54 (57.4%) had low income, 39 (41.5%) received authoritarian parenting and 46 (48.9%) had a poor diet. Then, there was a relationship of income (p = 0.0005), parenting (p = 0.0005) and diet (0.0005) toward stunting. In short, it can be concluded that there was a relationship between income, parenting and eating patterns toward stunting. It is expected that health workers provide counseling to the respondents and invite all parties to work together in reducing health problems. Keywords : Stunting, exclusive Breastfeeding, Parenting, Income, dietary habit